Verify the scene, report the symptoms: Testing the Verifiability Approach and SRSI in the detection of fabricated PTSD claims. (18th February 2019) - Boskovic, Irena; Dibbets, Pauline; Bogaard, Glynis; Hope, Lorraine; Jelicic, Marko; Orthey, Robin
Abstract : Purpose: In order to effectively feign post‐traumatic stress disorder, a person needs to confabulate an exposure narrative and to fabricate symptoms of high distress. The Verifiability Approach (VA) is a lie‐detection method based on the notion that truth tellers' narratives include more verifiable (checkable) information than liars' narratives. The Self‐Report Symptom Inventory (SRSI) is a measure of over‐reporting, and it includes genuine symptoms and pseudosymptoms that are likely to be endorsed in fabricated symptom reports. In this study, we examined whether the VA can help discriminate the fabricated exposure narratives, and whether the SRSI can aid screening for symptom over‐reporting. Method: One group of participants (truth tellers) witnessed a vehicle crash scene using the Virtual Reality paradigm ( n = 22), while the other group (feigners) was instructed to fabricate such an experience ( n = 46). All the participants wrote the exposure narratives and completed the SRSI. Results: Feigners produced non‐verifiable (vague) and lengthier narratives than truth tellers, who reported a higher proportion of checkable information. Regarding the symptom reports, feigners endorsed more of trauma‐related genuine symptoms and pseudosymptoms than truth tellers. Conclusion: The non‐verifiable details and the proportion of verifiable details, together with the SRSI subscales, can assist explaining the reporting strategies of those feigning negative exposures.